Friends, neighbours and village cereal stockists: hope for non-hybrid seed access? - Njuguna-Mungai, Esther (International Crops Research Institute for the Semi-Arid Tropics, 2019)
Presented by Esther Njuguna-Mungai (CGIAR Research Program on Grain Legumes and Dryland Cereals) on 21 November 2019, as part of the webinar 'Gender dynamics in formal seed systems in Sub-Saharan Africa and worldwide lessons'. The webinar was co-organized by the CGIAR Collaborative Platform for Gender Research and CGIAR Research Program on Maize.